Occurrence of the South American Tomato Leaf Miner, Tuta absoluta (Meyrick) in Southern Shan, Myanmar - Sopana Yule (MDPI AG, 2021)
The South American tomato leaf miner, Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae), one of the most important invasive insect pests affecting tomato production worldwide, was for the first time detected in Myanmar. Preliminary surveys on pest occurrence on tomato crops in Myanmar suggested the presence of T. absoluta in Southern Shan State, but there was no official survey conducted until the end of 2019. Therefore, this study aimed to confirm the presence of T. absoluta in Myanmar. The presence of T. absoluta was specifically observed in the Southern Shan State, which is the largest tomato production area in Myanmar, where tomato is grown under two cultivation methods, floating and land cultivation. The highest T. absoluta infestation was recordedat Kalaw with (82%), followed by Inle Lake (i.e., floating cultivation) (20%) and Pin Ta Ya (10%). The amount of T. absoluta larvae was significantly higher in the lower third of the plants, followed by the middle section and upper section, respectively, in three fields surveyed. Potential and severe economic damage may be expected if management practices are not in place to reduce the presence of this invasive pest. It is of immediate importance that plant protection and quarantine offices of ASEAN member states coordinate their response to T. absoluta and build their capacity to monitor the pest and develop a strategy for when it arrives. In addition, a suitable management strategy is needed to reduce the occurrence of this invasive pest.